If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7 = 3w + -4 Reorder the terms: -7 = -4 + 3w Solving -7 = -4 + 3w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-3w' to each side of the equation. -7 + -3w = -4 + 3w + -3w Combine like terms: 3w + -3w = 0 -7 + -3w = -4 + 0 -7 + -3w = -4 Add '7' to each side of the equation. -7 + 7 + -3w = -4 + 7 Combine like terms: -7 + 7 = 0 0 + -3w = -4 + 7 -3w = -4 + 7 Combine like terms: -4 + 7 = 3 -3w = 3 Divide each side by '-3'. w = -1 Simplifying w = -1
| 11x-12=6x-2 | | 15b^2+10b-8= | | 3(n-6)=8+4n | | .75x+8=x | | 0=x*2-x-30 | | -6=y+3 | | 10+4x=-14+6x | | 15b^2+10b-8=0 | | .75x+8=f(x) | | u-5=-8 | | sin(4x)=1 | | 5=-21+3t | | 6+w=-2 | | (7x+4)(3x+9)= | | y=226-33x | | -36+6x=12 | | 3.6x+8=26 | | n-10=-27 | | 1.25g+4=13.5 | | a^2-x=0 | | 12-4h=6 | | j-(-17)=30 | | 5-3*x=20 | | t+13.4=-4.5 | | 1p-5=8 | | 4(p+5)=7 | | 36t^2=9 | | -6n+5n=-3 | | 4(p+-5)=7 | | (6x-6)(4x+9)=0 | | -6r+5s+2t=-11 | | 3(x)=8.25 |